2013
DOI: 10.1261/rna.036665.112
|View full text |Cite
|
Sign up to set email alerts
|

The T. brucei TRM5 methyltransferase plays an essential role in mitochondrial protein synthesis and function

Abstract: All tRNAs undergo post-transcriptional chemical modifications as part of their natural maturation pathway. Some modifications, especially those in the anticodon loop, play important functions in translational efficiency and fidelity. Among these, 1-methylguanosine, at position 37 (m 1 G 37 ) of the anticodon loop in several tRNAs, is evolutionarily conserved and participates in translational reading frame maintenance. In eukaryotes, the tRNA methyltransferase TRM5 is responsible for m 1 G formation in nucleus-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…TrmD catalyzes methyl transfer to the N1 atom of G37 in eubacterial tRNA (24). The m 1 G37 modification in archaea (54 -56), eukaryotes (57,58), and mitochondrial (59,60) tRNA is conferred by Trm5, which belongs to the class I enzymes. Thus, the same modification at the same position in tRNA is conferred by different enzymes, namely TrmD (class IV) and Trm5 (class I), according to the organism.…”
Section: Discussionmentioning
confidence: 99%
“…TrmD catalyzes methyl transfer to the N1 atom of G37 in eubacterial tRNA (24). The m 1 G37 modification in archaea (54 -56), eukaryotes (57,58), and mitochondrial (59,60) tRNA is conferred by Trm5, which belongs to the class I enzymes. Thus, the same modification at the same position in tRNA is conferred by different enzymes, namely TrmD (class IV) and Trm5 (class I), according to the organism.…”
Section: Discussionmentioning
confidence: 99%
“…We localized Arabidopsis TRM5 to the nucleus which is in contrast to the cytoplasmic and mitochondrial localisation in other eukaryotes: Trypanosoma brucei, Homo sapiens (HeLa cells) and Saccharomyces cerevisiae (11,23,29), although in one study S. cerevisiae Trm5 has also been localized exclusively to the nucleus (53).…”
Section: Discussionmentioning
confidence: 73%
“…The discovery of m 1 G and m 1 I at position 37 in tRNAs of a wide range of eukaryotic and prokaryotic organisms underscores its importance as a key regulator of tRNA function and, presumably, translation (11,20,23). Previous studies in bacteria have shown that m 1 G37 is required for translational fidelity (20,57,58) and that mutations in the enzymes catalyzing m 1 G37 severely impact growth or cause lethal phenotypes (11,23,29). In eukaryotes, m 1 G37 modification requires the methyltransferase TRM5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations